Perancangan Aplikasi E-Query Berbasis Website Dengan Menerapkan Algoritma Two Way Untuk Mencari Istilah-Istilah Dasar Pada Structur Query Language (SQL) - Lase, Faatulo (Jurnal Ilmu Komputer, Teknologi Dan Informasi, 2023)
Usually in an application that is created and used to process data, the application is never separated from a database. In making applications that already use the database, there will be SQL (Structure Query Language) commands to process data on the application, for example in the process of storing data, editing data and deleting data. If someone wants to make an application and doesn't understand the terms of SQL used in processing data, then there will be confusion in making the application. The problem that often occurs when creating and designing an application is that there are difficulties in defining and knowing the functions of the queries that exist in Sql itself. Many people experience confusion in using commands or terms in SQL so that confusion in using terms will have an impact on the estimated time that has been determined in building an application. E-Query application development This will help many parties in searching and using basic SQL commands. Two Way Algorithm is an algorithm used to search basic SQL commands on Website-Based E-Query applications.